PRODUKTIVITAS DAN PENDAPATAN USAHATANI PADI LOKAL VARITAS MAYANG DI DESA MALINTANG LAMA KABUPATEN BANJAR Produvtivity and income of farming local padi variety mayang in Malintang Lama village Banjar regency. - Subhan Fitriadi; Eddy Triatmoko (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
The purpose of this research is to know the revenue,the eksplicit cost ,income and prodictivity  of  padi mayang variety farming. This research was conducted in Februari –April 2020 at village Malintang Lama, , Banjar regency.    The simple random sampling methode used was by observing 28  farmers in  village Malintang Lama who planted padi. The Average result of the revenue is Rp16.537.500,00/farmer., the average Eksplicit cost is  Rp. 6.629.455,35/farmer, and Average income Rp. 9.908.044,647/farmer .and Productivity 2,6 Ton/Ha   From  this result of development of farming padi mayang variety we believe that it has good prospect and revenue, of the average income ,tecnicall and economically.